Importance of keep being healthy with cranberries dry fruit to prevent UTIs / Nadia Aliya Mohamad Adrus - Mohamad Adrus, Nadia Aliya (Faculty of Art and Design, 2020)
Urinary tract infections (UTIs) is the most common bacterial infection in women and people does not aware regarding improper diet in lifestyle.